2020
DOI: 10.1194/jlr.ra119000479
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 reduces allopregnanolone synthesis in the brain and contributes to age-related cognitive decline in mice

Abstract: Cognitive decline with age is a harmful process that can reduce quality of life. Multiple factors have been established to contribute to cognitive decline, but the overall etiology remains unknown. Here, we hypothesized that cognitive dysfunction is mediated, in part, by increased levels of inflammatory cytokines that alter Allopregnanolone levels, an important neurosteroid in the brain. We assessed the levels and regulation of allopregnanolone and the effects of allopregnanolone supplementation on cognitive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Our results demonstrated the prominent therapeutic effect of Allopregnanolone on working spatial memory, evidenced by the significant improvement of alternation score in the Allopregnanolone group compared to the MetS group ( Figure 1 ). These results are concomitant with the study done by Park et al, [ 6 ], who assessed the effect of Allopregnanolone on spatial learning and memory in aged mice using the radial arm water maze. Additionally, Frye et al [ 44 ] demonstrated that Allopregnanolone administration improved T-maze and water maze task performance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results demonstrated the prominent therapeutic effect of Allopregnanolone on working spatial memory, evidenced by the significant improvement of alternation score in the Allopregnanolone group compared to the MetS group ( Figure 1 ). These results are concomitant with the study done by Park et al, [ 6 ], who assessed the effect of Allopregnanolone on spatial learning and memory in aged mice using the radial arm water maze. Additionally, Frye et al [ 44 ] demonstrated that Allopregnanolone administration improved T-maze and water maze task performance.…”
Section: Discussionsupporting
confidence: 87%
“…Neurosteroids are steroid hormones synthesized de novo in the brain and peripheral nervous tissues [ 5 ]. Allopregnanolone is an essential neurosteroid in the brain, synthesized locally or in the periphery, and reaches the brain by crossing the blood-brain barrier [ 6 ]. Allopregnanolone levels were reported to be downregulated in neurodegenerative diseases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the assessment of ''age-related cognitive impairment'' is a critical scientific research area in human disease. Recent evidence of cognitive impairment in a mouse model of accelerated aging using the PhenoTyper indicates the translational potential for assessing cognitive function in various models of aging and models designed to mitigate age-related changes in learning and memory (Logan et al, 2019;Parks et al, 2020). In addition, when standard measurements like the Cumulative Learning Index (Logan et al, 2019) are proved to be…”
Section: Measuring Learning and Cognitive Functionsmentioning
confidence: 99%
“…Interestingly, allopregnanolone, a progesterone metabolite, can inhibit proinflammatory processes through modulating GABA receptors (Balan, Beattie, O'Buckley, Aurelian and Morrow, 2019), while IL-6 decreases allopregnanolone synthesis in the brain ( Parks et al., 2020 ). While estrogen deficiency has been suggested as a risk for depressive behavior in animal models ( Xu, Sheng, Tang, Lu and Ni, 2015 ), estrogen has also been shown to increase during acute stress in humans ( Pletzer, Poppelaars, Klackl and Jonas, 2021 ).…”
Section: Biological Changes In the Perinatal Period With Potential Importance To Mood Changesmentioning
confidence: 99%